Relaxin binding in the rat heart atrium. - Osheroff, P L (1992)
Relaxin is a member of the insulin family of polypeptides that is best known as a reproductive hormone. In an effort to elucidate the mechanism of action of relaxin we previously localized the specific binding sites of a 32P-labeled relaxin in the rat uterus and brain. These studies suggested that, in addition to its classical role in pregnancy, relaxin might have other physiological functions. In the present paper we describe the specific and high-affinity binding of relaxin to the cardiac atrium of both male and female rats. The relaxin binding could not be displaced by peptides belonging to the same family [insulin, insulin-like growth factor I (IGF-I)] or by peptides that were identified in the atrium or were known to have cardiovascular functions (atrial natriuretic peptide, angiotensin II). The dissociation constant for relaxin in the atrium was estimated to be 1.4 nM, which was similar to that found in the uterus (1.3 nM) and the brain (1.4 nM). In view of the close association of relaxin with reproduction, an experiment was also performed to compare the relaxin binding in the uterus and heart after gonadectomy and sex steroid treatment. It was found that the relaxin binding in the rat uterus was diminished by 53% overall following ovariectomy but was restored to 90% of normal levels when treated with estrogen (but not with testosterone). In contrast, the relaxin binding in the rat heart was not affected by castration or sex steroid treatment. We conclude that specific and high-affinity relaxin receptors exist in the atrium of both the male and female rat heart and that these are regulated differently than the relaxin receptors in the uterus.